Finding Your Voice: Penguatan Keterampilan Public Speaking Bagi Siswa SMA Negeri 1 Wonosari - Api Adyantari; Vonezyo Yupanzara Dharomesz; Aloysia Desy Pramusiwi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Public speaking is an essential skill for students in academic, social, and future professional contexts. This community service program aimed to strengthen the confidence and public speaking skills of Grade 10 students at SMA Negeri 1 Wonosari. Conducted on 6–9 January 2026 in three classes, the program comprised needs assessment, material development, interactive training, and formative evaluation. The materials covered speaking styles and speaker personas, verbal-vocal-visual delivery, audience engagement, and effective self-introduction techniques. Students participated in discussions, demonstrations, individual exercises, speaking practice, and feedback sessions. Evaluation was conducted descriptively through facilitator observations, student responses, and practice performance. The results showed that students could identify suitable speaking styles and personas, recognize key elements of effective delivery, and present more distinctive self-introductions. Several students also showed willingness to speak before their peers. Repeated practice and pretest-posttest assessment are recommended for future programs.